Multisystem inflammatory syndrome in children during the COVID-19 waves: data from the Juvenile Inflammatory Rheumatism cohort - Kechiche, Robin; Borocco, Charlotte; Bajolle, Fanny; Belot, Alexandre; Poignant, Sylvaine; Lachaume, Noémie; Percheron, Lucas; Meinzer, Ulrich; Mertes, Clara; Despert, Véronique; Morin, Luc; Lambert, Virginie; et al. (Frontiers in Pediatrics, 2023)
Introduction Multisystem inflammatory syndrome in children (MIS-C) is a new condition that first appeared in children and adolescents during the COVID-19 pandemic. We aimed to describe the diagnostic course, clinical and biological manifestations, and treatment of MIS-C during the first three COVID-19 waves. Methods We extracted patient data from the Juvenile Inflammatory Rheumatism (JIR) cohort. We analyzed data for patients meeting the World Health Organization diagnostic criteria for MIS-C from the start of the COVID-19 pandemic in March 2020 to 30 June 2021. We then compared data for patients in wave one to those in waves two and three. Results We identified 136 patients with MIS-C. The median age decreased but not significantly during the waves, from 9.9 years to 7.3 years (p=0.105). Boys represented 52.2% (n=71) of patients, and 46% (n=41) of patients originated from sub-Saharan Africa (p<0.001). Patients presented fewer diarrhea (p=0.004), respiratory distress (p<0.001), and myocarditis (p<0.001) with progressive waves. Biological inflammation also decreased, namely C-reactive protein level (p<0.001), neutrophil count (p=0.004), and albumin level (p<0.001). Patients received more corticosteroids (p<0.001) and required less ventilation support (p<0.01) and less inotrope treatment (p<0.001) in the later waves. The duration of hospitalization gradually decreased (p<0.001), as did critical care unit admissions (p=0.002). Conclusion Over the three COVID-19 waves, with a change in management of MIS-C, children in the JIR cohort in France showed a less severe disease course, in particular, a greater use of corticosteroids. This observation may reflect the impact of both improved management and different SARS-CoV-2 variant.